Analysis of Arabic against The Use of Artificial Intelligence (AI) through Tashkeel (Automatic Harokat) Application to Increase Maharah Qiraah - Fahraini, Sovia; Almaliki, Muhammad Fikri (Proceeding International Conference on Education, 2023)
Artificial Intelligence (AI) has the goal of making machines smarter and providing significant changes towards practical application. One of the AI ​​is the tashkeel application which is used to automatically give a vowel to an Arabic text by writing or pasting Arabic text and it will automatically be honored. However, not all practical tools give scientifically correct results. Sometimes there are differences in terms of syntax or the study of words and groups of words that form a phrase, clause and sentence. Because, it is known that the application is a tool without knowing the scientific basis so that it gives a sense of doubt about the correctness of the results. So that the researcher analyzes how the syntax errors or mistakes in compiling the linguistic structure in Arabic so that it is in accordance with the nahwu rules. It is intended that in the future, the Tashkeel application can be used by the general public without any doubts. This research uses literature study method through several books, journals and analysis from various related sources. So that the data obtained is that the harokat obtained through the tashkeel application is considered correct in accordance with the rules of Arabic nahwu, then the community, especially students or students, can easily use the application to improve maharah qiraah.